Energy storage and return in sport surfaces - Baroud, G.; Nigg, B. M.; Stefanyshyn, D. (Sports Engineering, 1999)
The purpose of this paper was to determine the energy input, return and dissipation of sport surfaces using the FE analysis based on actual ground reaction forces. A three-dimensional finite element model of an existing running track was created. A viscoelastic material model was implemented using experimentally determined parameters from existing surface samples. Ground reaction forces collected during forefoot running were input into the model and used to determine the associated energetics of the surface. This method has the advantage, over previous experimental methods, of characterising the energy associated with sport surfaces under actual loading conditions experienced during human movement.